An assessment of MNCs distributors capability for performance improvement - Quek, Theng Theng (2019)
This dissertation is an empirical study of multi-national company’s (MNC) distributors capability assessment, which discusses expectation of MNCs with regards to its distributor and suggests ways that MNCs could effectively assess the distributors capabilities for performance improvement. This study is backed by the data from a US based MNC which could be leveraged by other MNCs to discover insights on distributors capabilities and measures to improve performance for order growth. It provides an up-to-date, comprehensive synthesis and evaluation of the existing literature on multinational firms and their distributors. Through a chronological description comparing traditional researches and most recent reviews, it presents the authors findings and understanding of the business relationship for a firm with its distributors. With the knowledge acquired, data from the company is mapped to the adapted assessment model, analyzed and applied in solving a real-life business problem. At the end of data analysis, analysis was made based on the findings and lessons learnt for distributors management optimization and ensuring sustainable order growth were discussed. Overall, the goal of this empirical study is to enable a MNCs or small to medium enterprises (SME) to leverage the model and learnings to assess the performance of distribution channel partners, identify gaps and opportunity, with the goal to grow order ultimately.